Safety and efficacy of donepezil hydrochloride in patients with mild to moderate Alzheimer's disease: Findings of an observational study - Mehta, Suyog (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Alzheimer's disease (AD), a progressive brain disorder, is the most common cause of dementia among the elderly. Donepezil hydrochloride is a potent, reversible, and highly selective inhibitor of acetylcholinesterase (AChE). It is chemically distinct from other cholinesterase (ChE) inhibitors which are effective in the treatment of AD. OBJECTIVES: To evaluate the safety and efficacy of donepezil hydrochloride therapy over a 12 weeks period in patients with mild to moderate AD in Indian population. MATERIALS AND METHODS: In this post-marketing study, patients with mild to moderate AD received oral donepezil hydrochloride 5 mg/day for 4 weeks followed by 10 mg/day for 8 weeks. Patients were assessed 4 times weekly for cognition on ‘Mini Mental Status Examination (MMSE) scale’, and function on ‘Activities of Daily Living (ADL) index’. Clinicians and caregivers assessment of safety and efficacy was assessed on a 5-point rating scale. RESULTS: One hundred and seventy two of one hundred and eighty two patients completed 12 weeks of study period. MMSE score significantly improved (P<0.0001) from 16.72 at baseline to 19.77 after 12 weeks, and there was significant improvement (P<0.05) in ADL index in 13 of 17 domains after 12 weeks. Caregivers and clinicians rated the therapy as very good to good in >80% and >90% patients, respectively. Adverse events were consistent with the known pharmacological and safety profile of donepezil. CONCLUSIONS: Donepezil is well tolerated in Indian patients with mild to moderate AD with significant improvement in cognition and function.